Factors Affecting The Economic Recession and its potential in Indonesia Due To Covid-19 Pandemic - Ilyas, Fadli (International Journal of Social and Management Studies, 2022)
This study was conducted to find out what factors caused an economic recession and the potential for an economic recession as a result of the prolonged Covid-19 pandemic. Various strategies are launched, policies are implemented, socialization is carried out until slogans are echoed so that Indonesia can recover faster and rise stronger. For this reason, it is hoped that all parties and elements of society can work well together so that this policy package can run optimally so that the recovery of various aspects, especially the economic aspect, must be immediately restored. These economic recession factors will be reviewed in a SWOT analysis to provide an overview of the success and anticipation of the policies taken by the government